Seismic performance test of rammed earth wall with different structural columns. Issue 1 (January 2021) - Zhou, Tiegang; Zhang, Zaiyu; Su, Zhifan; Tian, Peng
Rammed earth wall load-bearing dwellings are widely distributed in western China. Rammed earth has the advantages of warm in winter and cool in summer, and it is a kind of sustainable construction material. In recent years, in previous earthquakes, the collapse of rammed earth buildings is serious, resulting in huge losses of personnel and property. To improve the seismic performance of rammed earth buildings and retain the characteristics of local buildings, a reinforcement measure with additional structural columns is proposed in this article. Three kinds of structural columns are designed, which are cast-in-place concrete, square steel tube, and concrete-filled square steel tube core column. Through the quasi-static experimental study on the rammed earth wall, the effects of different structural columns on the failure shape, bearing capacity, deformation capacity, and energy dissipation capacity of the wall are compared. The test results show that adding structural columns on both sides of the wall can effectively restrain the rammed earth wall, restrain its brittle failure, significantly improve the energy dissipation capacity of the wall, and obviously improve the seismic performance of the wall. This measure is applicable to rammed earth buildings and provides theoretical support for improving the seismic performance of traditional dwellings.